Frequency analysis of subgroup blood typing and Cis-AB type - Baek, Youngdu; Park, Cheolin (Asian Journal of Pharmaceutical Research and Development, 2023)
The purpose of this study is to prevent side effects of transfusion by analyzing the frequency of subtype blood types in blood type tests. Of the 19,800 cases, 128 (0.59%) cases were classified as subtypes. The distribution of subtype detection in K University Hospital was classified as Cis-AB (39 cases, 30.5%), A₂ (25 cases, 21.6%), A₂B (24 cases, 20.7%), A₁B (13 cases, 11.2%), A₃ (11 cases, 9.5 cases) %), B₃(9 cases, 7.8%), Ag(3 cases, 2.6%), Ax(1 case, 0.95%), Ay(1 case, 0.9%), Bx(1 case, 0.9%), Bel(1 case, 0.9%). Am, Az, and Bm were not detected at all. These subtype blood types are caused by quantitative and qualitative variants of antigenicity on the surface of red blood cells. Finally, the examiner should select blood that matches the patient's blood type and select blood that is not abnormal in the examination and transfuse it to prevent side effects of transfusion in advance.